Padlet for MIS Course: measuring its usability and quality in teaching and learning / Wan Aryati Wan Ghani and Haslinda Noradzan - Wan Ghani, Wan Aryati; Noradzan, Haslinda (UiTM Press, 2022)
Since the Covid-19 pandemic, most higher education institutions in Malaysia and elsewhere have embraced open and distant learning (ODL). Students must be engaged in the teaching and learning process for the learning process to continue. As a result, technology is on the approach of replacing traditional face-to-face classes with virtual classrooms. Students and lecturers are the most important stakeholders, and they must work together. The learning environment for the Management Information Systems (MIS) course in particular, must be engaging and enjoyable. Therefore, this study proposes Padlet as a learning tool for a comprehensive learning experience that is suitable for both synchronous and asynchronous teaching and learning. This study seeks to examine the quality and usability of Padlet from the perspective of lecturers and students. It also investigates their experience when they use Padlet in teaching and learning. The nature of Padlet itself offers interesting and fun learning. Based on the survey conducted among students enrolling in this course and lecturers teaching MIS, Padlet appears to be engaging, interesting, and easy to use as it provides a shorter and quicker way to access learning materials. Its simplicity offers a great way for teachers and students to collaborate.